Evaluating The Effectiveness : A Legal Protection for Child Victims of Economic Exploitation in Informal Street Labor in Indonesia - Dzikrina Aulia; Rahaditya (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2025)
Abstract Purpose – This study evaluates the effectiveness of legal protection for children who are victims of economic exploitation in street environments based on Law Number 35 of 2014 concerning Child Protection. The research addresses the ongoing gap between legal norms and their implementation, which results in insufficient protection for street children. Method – A socio-legal approach was employed by integrating literature review, semi-structured interviews, and field observations. Data were analyzed qualitatively using Philipus M. Hadjon’s theory of legal protection and Soerjono Soekanto’s theory of legal effectiveness to examine how legal instruments operate in practice and how institutional coordination influences child protection efforts. Result – The findings show that although child protection regulations in Indonesia are normatively strong, their implementation remains ineffective. Weak inter-agency coordination, a shortage of social workers, and low public awareness significantly hinder efforts to prevent and address economic exploitation in street environments. These limitations prevent the realization of the best interest of the child. Implication – The study emphasizes the need to strengthen institutional capacity, improve coordination among agencies, expand the number of professional social workers, and enhance public awareness regarding child protection. It also highlights the importance of integrating restorative justice approaches to ensure holistic recovery for child victims. This study makes a practical contribution by recommending the strengthening of inter-agency coordination, increasing the number of professional social workers, and integrating restorative justice approaches to ensure holistic recovery for child victims.